Surgical outcomes of re-excimer laser phototherapeutic keratectomy (re-PTK) - Osamu Hieda (Nature Portfolio, 2021)
Abstract To assess the surgical outcomes of re-excimer laser phototherapeutic keratectomy (re-PTK) for recurrent disease after initial PTK. Retrospective cohort study with historical comparison group. This study involved 56 patients who underwent re-PTK (mean follow-up period: 47.9 ± 36.2 months) at the Baptist Eye Institute, Kyoto, Japan. In all subjects, corrected-distance visual acuity (CDVA) before and after re-PTK was compared. Postoperative recurrence of corneal lesion with a decrease of CDVA of two lines or more was compared with postoperative best CDVA deemed as a significant relapse. The Kaplan–Meier method was used to compare the recurrence rate post-re-PTK with that after the initial PTK. The disease classification in the 78 eyes was heterozygous-type GCD (hetero-GCD, n = 47 eyes), homozygous-type GCD (homo-GCD, n = 13 eyes), band keratopathy (n = 7 eyes), lattice corneal dystrophy (n = 6 eyes), and other (n = 5 eyes). After re-PTK, homo-GCD recurred statistically significantly earlier than hetero-GCD (P = 0.0042). No significant difference was found in the recurrence rate for all diseases between post-re-PTK and post initial PTK (P > 0.05). Surgical outcomes after re-PTK were nearly equal to those after initial-PTK.